Faktor Risiko Masalah Mental Emosional Pada Anak Prasekolah Di Kota Sukabumi - Shinta Utami; Dewi Hanifah (Pusat Penelitian dan Pengembangan Humaniora dan Manajemen Kesehatan, 2021)
Impairment of mental and emotional development in children can be an early sign of crime at a young age. Risk factors for mental and emotional disorders in children are influenced by external and internal factors. This study aims to determine the prevalence and factors influencing mental-emotional problems in pre-school children in Sukabumi City in 2020. The study design was cross-sectional. The number of samples of pre-school children is 385 children. The data was collected with the help of a checklist and a questionnaire on psychological emotional problems (KMME). Logistic regression was used in the data analysis. The result of the prevalence of mental emotional disorders is 25.7% (99 children). The results of the multivariate analysis showed that emotional psychological problems in children caused by authoritarian upbringing [OR = 5.88 (95% CI; 3.45-10.02)], birth complications [OR = 3.36 (95% CI); 1.95-5.81)] is affected. , divorced parents [OR = 3.00 (95% CI; 1.09–8.23)], working mother [OR = 1.77 (95% CI; 1.04–3.00)] and mother with a low level of education [OR = 1.74 (95% CI; 1.02–2.95.))], authoritarian upbringing is the dominant factor in emotional psychological problems in children. Routine detection by health workers is required so that mental emotional problems in children can be detected as early as possible. Abstrak Perkembangan mental emosional anak yang terganggu dapat menjadi tanda awal kejahatan pada usia remaja. Faktor risiko masalah mental dan emosional pada anak dipengaruhi faktor eksternal dan internal. Studi ini bertujuan untuk mengetahui prevalensi dan faktor-faktor yang mempengaruhi masalah mental emosional pada anak prasekolah di Kota Sukabumi pada tahun 2020. Disain studi potong lintang. Jumlah sampel anak prasekolah adalah 385 anak. Pengambilan data dilakukan dengan menggunakan daftar ceklist dan juga kuesienor masalah mental emosional (KMME). Analisis data menggunakan regresi logistik. Hasil prevalensi masalah mental emosional sebesar 25,7% (99 anak). Hasil analisis multivariat menunjukkan bahwa masalah mental emosional terdapat pada anak dipengaruhi oleh pola asuh otoriter [OR =5,88 (CI 95%;3,45-10,02)], komplikasi saat lahir [OR=3,36 (CI 95%;1,95-5,81)], orangtua bercerai [OR=3,00 (CI 95%; 1,09-8,23)], ibu bekerja [OR= 1,77 (CI 95%;1,04-3,00)], dan pendidikan ibu rendah [OR=1,74 (CI 95%; 1,02-2,95)], Faktor yang paling dominan terhadap masalah mental emosional anak adalah pola asuh otoriter. Perlu dilakukan deteksi secara rutin oleh tenaga kesehatan agar masalah mental emosional pada anak dapat terdeteksi sedini mungkin.